Here we like playing princesses – newcomer migrant children's transitions within day care: exploring role play as an indication of suitability and home and belonging. Issue 2 (4th March 2017) - Kalkman, Kris; Clark, Alison
ABSTRACT: Using the concept of suitability to describe newcomer migrant children's connection to multiple fields of social and cultural relations, we explore a newcomer migrant girl's transition from an introductory group for migrant children with a refugee background into a mainstream day-care group. Inspired by sociocultural and transitional research, we assume that newcomer migrant children can fall into a liminal phase due to the loss of cultural references. Framed around the situated and contextualised nature of the girl's remembering and reconstructing of home and belonging through role play, we explore how roleplay discourses might be understood as cultural scripts or laminated productions reflecting particular representations of social and cultural attachment.